Perkawinan Beda Agama Menurut Peraturan Perkawinan di Indonesia Dihubungkan dengan Putusan Mahkamah Agung - Muhamad Arsy Surya Saputra; Lina Jamilah (UNISBA Press, 2022)
Abstract. Marriage is the inner birth bond between a man and a woman Marriage is a bond born bathin between a man and a woman as a husband and wife with the aim of forming a happy and eternal family based on the Supreme Godhead. To achieve the goal of marriage, it should be done by an adult. In Article 2 shrimp law No. 16 of 2019 on changes to Law No. 1 of 1974 on marriage mentions that marriage is legal if according to their respective religions are valid. But if the candidates for religious differences, then the prospective spouses can apply to the local District Court, the application to the District Court must be proven by the rejection of the Population Office and civil records in the city. District Court Judges use the Precedent of Supreme Court decision No. 1400 K / pdt / 1986 in his ruling in the granting of marriage licenses of different religions in Indonesia. This method of approach is normative juridical, i.e. conducting a positive legal inventory of marriage. This type of research is qualitative research, which is data collection with the intention of interpreting the phenomenon of granting permission for the implementation of different religious marriages that occur. The research specification is descriptive analysis, which focuses on the judgment of judges in granting requests for the implementation of marriages of different religions. The purpose of this study is to find out the implementation of marriages of different religions. The results of the study showed that there is no regulation governing marriages of different religions so that judges in granting marriages of different religions assume a legal void, and judges use the Supreme Court decision No. 1400 K / pdt / 1986 in consideration of his ruling ABSTRAK. Perkawinan ialah ikatan lahir batin antara seorang pria dengan seorang wanita Perkawinan ialah ikatan lahir bathin antara seorang pria dengan seorang wanita sebagai suami isteri dengan tujuan membentuk keluarga yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Untuk mencapai tujuan perkawinan, hendaknya dilakukan oleh orang dewasa. Dalam Pasal 2 Udang-Undang Nomor 16 tahun 2019 tentang perubahan atas Undang-Undnag nomor 1 tahun 1974 tentang perkawinan menyebutkan bahwa perkawinan adalah sah jika menurut agama nya masing-masing sah. Namun jika oara calon pasasangan terdapat perbedaan agama, maka para calon pasangan tersebut dapat mengajukan permohonan ke Pengadilan Negeri setempat, permohonan ke Pengadilan Negeri tersebut harus di buktikan dengan adanya penolakan dari Dinas Kependudukan dan catatan sipil di kota tersebut. Hakim Pengadilan Negeri menggunakan Preseden putusan Mahkamah Agung Nomor 1400 K/pdt/1986 dalam putusan nya dalam pemberian izin perkawinan beda agama di Indonesia. Metode pendekatan ini adalah yuridis normatif, yaitu melakukan inventarisasi hukum positif tentang perkawinan. Jenis penelitian ini adalah penelitian kualitatif, yaitu pengumpulan data dengan maksud menafsirkan fenomena pemberian izin pelaksanaan perkawinan beda agama yang terjadi. Spesifikasi penelitian adalah deskriptif analisis, yaitu memusatkan perhatian kepada pertimbangan hakim dalam mengabulkan permohonan pelaksanaan perkawinan beda agama . Tujuan penelitian ini adalah Untuk mengetahui pelaksanaan perkawinan beda agama. Hasil penelitian menunujukan bahwa tidak adanya peraturan yang mengatur tentang perkawinan beda agama sehingga Hakim dalam mengabulkan perkawinan beda agama beranggapan adanya kekosongan hukum, dan hakim menggunakan putusan Mahkamah Agung Nomor 1400 K/pdt/1986 dalam pertimbangan putusan nya